Analysis of Marketing Management Strategy and Economic Factors on MSME Sales Growth: Multiple Regression Analysis - Amril; Muammar Rinaldi; Richna Handriyani; Rifqah Harahap; Hilma Harmen (Outline Publisher, 2025)
This study aims to examine the influence of marketing management strategies and economic factors on the sales growth of Micro, Small, and Medium Enterprises (MSMEs) in Indonesia using multiple regression analysis. The variables analyzed include product strategy, pricing, promotion, distribution, inflation, interest rates, and per capita income. Data were collected through interviews, observations, and document analysis involving selected MSME owners and relevant secondary sources. The results reveal that all variables have a significant impact on sales growth, with per capita income and promotional strategies showing the strongest influence. The analysis also indicates that internal business strategies, when aligned with favorable macroeconomic conditions, contribute to consistent sales increases. Additionally, the adoption of digital marketing tools and improved access to financial resources have strengthened MSMEs' competitiveness in the marketplace. The study underscores the importance of a holistic approach that integrates both marketing strategies and economic trend monitoring for sustainable MSME growth. These findings offer practical implications for policymakers and business owners in designing strategies that support MSME development in dynamic economic environments. Further research is recommended to include a broader sample and explore sector-specific trends for deeper insights.